2022
DOI: 10.1007/s00213-022-06070-3
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study

Abstract: Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
(76 reference statements)
0
12
1
Order By: Relevance
“…In contrast, in 24 healthy individuals receiving either 600 mg CBD or placebo, no effects of acute CBD administration were found on emotional processing (using an fMRI paradigm based on neutral, fearful, and happy faces), cognitive activity (using a mental arithmetic task to measure emotional responses to stress and a face rating test with neutral, angry and happy expressions), and subjective response to experimentally induced anxiety [81]. The negative outcomes has been suggested to result from insufficient CBD blood concentrations, as CBD was administered in a fasted state, and several pharmacokinetic investigations indicate that the bioavailability of CBD without any food consumption is extremely low [82][83][84].…”
Section: Anxiolytic Effects Of Cannabidiol In Healthy Individualsmentioning
confidence: 81%
“…In contrast, in 24 healthy individuals receiving either 600 mg CBD or placebo, no effects of acute CBD administration were found on emotional processing (using an fMRI paradigm based on neutral, fearful, and happy faces), cognitive activity (using a mental arithmetic task to measure emotional responses to stress and a face rating test with neutral, angry and happy expressions), and subjective response to experimentally induced anxiety [81]. The negative outcomes has been suggested to result from insufficient CBD blood concentrations, as CBD was administered in a fasted state, and several pharmacokinetic investigations indicate that the bioavailability of CBD without any food consumption is extremely low [82][83][84].…”
Section: Anxiolytic Effects Of Cannabidiol In Healthy Individualsmentioning
confidence: 81%
“…These observations caution against relying on a single task to understand the role of individual differences in extended amygdala function in internalizing illness (73). They also caution against muddling 'threat-related' faces (emotion perception) and genuinely distress-eliciting stimuli (emotion generation), a practice which is routine in experimental studies of novel psychiatric therapeutics (74)(75)(76)(77). To the extent that uncertain-threat anticipation is key, it may be necessary to devise new paradigms that are more suitable for community and biobank samples-for instance, using aversive auditory stimuli or film clips.…”
Section: Discussionmentioning
confidence: 99%
“…These observations highlight the hazards of continuing to rely on a limited number of ‘workhorse’ neuroimaging paradigms to understand and predict emotion, temperament, and psychopathology ( Grogans et al, 2023 ). They also caution against muddling the distinction between the perception of threat-related cues and the actual experience of fear and anxiety, a practice that has become routine in therapeutics research ( Kwako et al, 2015 ; Schwandt et al, 2016 ; Paulus et al, 2021 ; Bloomfield et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although no intoxication or serious adverse events were observed, minor side effects, such as sleepiness/fatigue, increased energy, and dry mouth, were reported [ 182 ]. Brain imaging studies suggest that CBD anxiolytic effects could be due to its ability to decrease amygdala activation [ 183 ], even though a recent study reported that a single CBD administration (600 mg) did not modify brain responses to emotional faces, cognitive measures of emotional processing, or anxiety [ 184 ].…”
Section: Divergent Central Effects Of Thc and Cbdmentioning
confidence: 99%